The complete chloroplast genome sequence of the medicinal plant Crotalaria albida. Issue 6 (3rd June 2022) - Jiang, Chunyang; Hu, Lipan; Wu, Yingmei; Rui, Lu
Abstract: Crotalaria albida ( C. albida ) is a traditional Chinese medicinal plant that belongs to Fabaceae family. In this study, the complete chloroplast genome sequence of C. albida was sequenced. The genome is 152, 743 bp in length and includes two inverted repeat regions of 25, 535 bp. It was predicted to contain 127 genes in the chloroplast genome, among which 82 were protein-coding genes, 37 were tRNA genes, and 8 were rRNA genes. The maximum likelihood phylogenetic analysis based on 24 complete chloroplast genome sequences showed that C. albida was closely related to Ormosia semicastrata, Ormosia emarginata, and Ormosia xylocarpa.